Co-delivery of Siape1 and Melatonin by 125I-loaded PSMA-targeted Nanoparticles for the Treatment of Prostate Cancer - Liu, Ying; Hao, Lin; Dong, Yang; Dong, Bing-Zheng; Wang, Xin-Lei; Liu, Xing; Hu, Zheng-Xiang; Fang, Gao-Chuan; Wang, Guang-Yue; Qin, Jia-Xin; Shi, Zhen-Duo; Pang, Kun (Recent Patents on Anti-Cancer Drug Discovery, 2024)
Background: Both apurinic/apyrimidinic endodeoxyribonuclease 1 (APE1) inhibition and melatonin suppress prostate cancer (PCa) growth. Objective: This study evaluated the therapeutic efficiency of self-assembled and prostate-specific membrane antigen (PSMA)-targeted nanocarrier loading 125I radioactive particles and encapsulating siRNA targeting APE1 (siAPE1) and melatonin for PCa. Methods: The linear polyarginine R12 polypeptide was prepared using Fmoc-Arg-Pbf-OH. The PSMA-targeted polymer was synthesized by conjugating azide-modified R12 peptide to PSMA monoclonal antibody (mAb). Before experiments, the PSMA-R12 nanocarrier was installed with melatonin and siAPE1, which were subsequently labeled by 125I radioactive particles. In vitro biocompatibility and cytotoxicity of nanocomposites were examined in LNCaP cells and in vivo biodistribution and pharmacokinetics were determined using PCa tumor-bearing mice. Results: PSMA-R12 nanocarrier was 120 nm in size and was increased to 150 nm by melatonin encapsulation. PSMA-R12 nanoparticles had efficient loading capacities of siAPE1, melatonin, and 125I particles. The co-delivery of melatonin and siAPE1 by PSMA-R12-125I showed synergistic effects on suppressing LNCaP cell proliferation and Bcl-2 expression and promoting cell apoptosis and caspase-3 expression. Pharmacokinetics analysis showed that Mel@PSMA-R12-125I particles had high uptake activity in the liver, spleen, kidney, intestine, and tumor, and were accumulated in the tumor sites within the first 8 h p.i., but was rapidly cleared from all the tested organs at 24 h p.i. Administration of nanoparticles to PCa tumors in vivo showed that Mel@PSMA-R12- 125I/siAPE1 had high efficiency in suppressing PCa tumor growth. Conclusion: The PSMA-targeted nanocarrier encapsulating siAPE1 and melatonin is a promising therapeutic strategy for PCa and can provide a theoretical basis for patent applications.
Keywords: pharmacokinetics